An Analysis of Sentence Structure on A Game “Speak It Up!”: Systemic Functional Linguistic Study - Nina Hayuningtyas; Mega Fariziah N. H (JADEs Journal of Academia in English Education, 2022)
A linguistic study about Systemic Functional linguistics commonly analyzes the text in an article, journal, magazine, novel, or headline in a newspaper. However, the texts from a board game will be examined in this study. This study analyzed the mood system and sentence structure. The theories that Halliday and Matthiessen, 1992 on mood Analysis and the theory of Oshima and Hogue, 2007 are used to analyze the sentence structure. This study was qualitative research. The data are the text in every flash card in the “Speak It Up!” board game. The results of the study are, first, the declarative sentence was dominantly found in the study. Second, the results showed that the simple sentence was dominantly found. That means the language in every flash card is appropriate for children because the language is easy to understand.